Pore Microstructure Impacts on Lithium Ion Transport and Rate Capability of Thick Sintered Electrodes. Issue 6 (25th June 2021) - Nie, Ziyang; Parai, Rohan; Cai, Chen; Michaelis, Charles; LaManna, Jacob M.; Hussey, Daniel S.; Jacobson, David L.; Ghosh, Dipankar; Koenig, Gary M.
Abstract : Increasing electrode thickness is one route to improve the energy density of lithium-ion battery cells. However, restricted Li + transport in the electrolyte phase through the porous microstructure of thick electrodes limits the ability to achieve high current densities and rates of charge/discharge with these high energy cells. In this work, processing routes to mitigate transport restrictions were pursued. The electrodes used were comprised of only active material sintered together into a porous pellet. For one of the electrodes, comparisons were done between using ice-templating to provide directional porosity and using sacrificial particles during processing to match the geometric density without pore alignment. The ice-templated electrodes retained much greater discharge capacity at higher rates of cycling, which was attributed to improved transport properties provided by the processing. The electrodes were further characterized using an electrochemical model of the cells evaluated and neutron imaging of a cell containing the ice-templated pellet. The results indicate that significant improvements can be made to electrochemical cell properties via templating the electrode microstructure for situations where the rate limiting step includes ion transport limitations in the cell.